2023
DOI: 10.20961/carakatani.v38i2.75881
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Stock, Carbon Fraction and Nitrogen Fraction of Soil Under Bamboo (Dendrocalamus asper Back.) and Non-Bamboo Vegetation

Lintang Panjali Siwi Pambayun,
Benito Heru Purwanto,
Sri Nuryani Hidayah Utami

Abstract: <span lang="EN-US">The type of vegetation and soil organic matter affect the carbon fraction, nitrogen fraction and soil carbon stocks that contribute to the global carbon cycle. Therefore, the calculation of the composition of the fractions in different land covers is very important as a potential indicator of the effect of land management practices on soil organic carbon dynamics and supports the reduction of carbon dioxide (CO<sub>2</sub>) and soil carbon storage. This research aimed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The results of research by Arunrat et al [32] regarding the availability of C-organic in organic land that has been carried out for more than 5 years show that paddy fields treated with organic fertilizers have higher organic C than non-organic paddy fields, which is an average of 2.10-2.70%. C-organic is essential in soil clay content is supported by the opinion of Silalahi et al [33] that increasing soil organic carbon content can increase the activity of microorganisms in the soil, which can assist in the decomposition of minerals and assist in the formation of carbon chains in the soil [34]. The analysis results also revealed that organic, semi-organic and conventional rice fields have a dust fraction content that is not significantly different.…”
Section: Condition Physical Properties Of the Soilmentioning
confidence: 83%
“…The results of research by Arunrat et al [32] regarding the availability of C-organic in organic land that has been carried out for more than 5 years show that paddy fields treated with organic fertilizers have higher organic C than non-organic paddy fields, which is an average of 2.10-2.70%. C-organic is essential in soil clay content is supported by the opinion of Silalahi et al [33] that increasing soil organic carbon content can increase the activity of microorganisms in the soil, which can assist in the decomposition of minerals and assist in the formation of carbon chains in the soil [34]. The analysis results also revealed that organic, semi-organic and conventional rice fields have a dust fraction content that is not significantly different.…”
Section: Condition Physical Properties Of the Soilmentioning
confidence: 83%
“…Soil organic carbon can balance nutrient availability, increase soil aeration, increase water infiltration rate, and the soil's ability to store water (Bhattacharyya et al, 2022). Soil organic carbon is essential in improving soil health and sustainability in agriculture (Pambayun et al, 2023).…”
Section: Resultsmentioning
confidence: 99%